THE CONTRIBUTION OF THE MONTESSORI APPROACH TO MULTISENSORY APPROACHES TO EARLY LEARNING DISABILITIES - Jamieson, Natalie; Yolande (My University, 2006)
Learning disabilities have become of increasing concern for educators. More and more children are having difficulty learning to read and write. This dissertation investigates what constitutes a learning disability, its etiology and whether or not it is possible to identify these disabilities in early childhood. The investigation further aims to discover if these learning disabilities are comprised of sub-disabilities and if these can be identified as such. To this end the research aims to determine the most appropriate remedial intervention strategies used for learning disabilities. Multisensory intervention is therefore explored. On the basis of this the Montessori Method is examined to ascertain whether or not the method can contribute to multisensory intervention at the preschool level. It is argued that the Montessori Method is admirably suited to making such a contribution. Further empirical research for these claims is indicated.
Faculty of Humanities School of Education 9805090w NATALIE@WBS.CO.ZA
Keywords: learning Disabilities; Montessori method; Multisensory; Early childwood; preschool